Opioid-Sparing and Multimodal Analgesia in Cesarean Delivery: A Systematic Review of Evidence and Implementation Across High and Low-Middle Income Countries: A Systematic Review - Agastya, Wayan Dhea; Rahmadinie, Amalia (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
ABSTRACT Introduction: Cesarean delivery is a common surgical procedure worldwide, often accompanied by significant postoperative pain that can negatively impact recovery, early breastfeeding, and maternal mobility. Opioids have traditionally been central to post-cesarean analgesia but are associated with side effects such as nausea, vomiting, pruritus, sedation, and respiratory depression. Recently, opioid-sparing and multimodal analgesia strategies—combining neuraxial opioids, regional blocks (e.g., transversus abdominis plane [TAP] block), and non-opioid systemic agents (NSAIDs, acetaminophen)—have been increasingly adopted to reduce opioid consumption while maintaining effective analgesia. Methods: A systematic literature search was conducted in PubMed, Scopus, Web of Science, and Google Scholar for studies published from January 2021 to August 2025. Eligible studies included randomized controlled trials, cohort studies, and quality improvement projects evaluating opioid-sparing multimodal analgesia in women undergoing cesarean delivery in both high-income countries (HICs) and low- and middle-income countries (LMICs). Primary outcomes were postoperative opioid consumption and pain scores; secondary outcomes included opioid-related side effects, recovery milestones, maternal satisfaction, and neonatal safety. Data extraction and quality assessment were performed independently by two reviewers following PRISMA 2020 guidelines. Discussion: The review included nine studies from diverse settings. Multimodal analgesia regimens consistently reduced opioid consumption and pain scores, improved maternal satisfaction, and decreased opioid-related adverse effects. Regional techniques such as TAP block were effective adjuncts or alternatives to neuraxial opioids, especially in LMICs where opioid availability and monitoring are limited. Adoption of multimodal protocols was more widespread in HICs, often integrated within enhanced recovery after cesarean (ERAC) pathways. Barriers in LMICs included limited regional anesthesia expertise, drug availability, cost, and institutional protocols, highlighting the need for capacity building and context-specific guidelines. Conclusion: Opioid-sparing multimodal analgesia is effective, safe, and feasible across various healthcare settings, improving postoperative pain control and recovery after cesarean delivery. Addressing implementation gaps between HICs and LMICs through training, resource allocation, and simplified protocols is essential to optimize global obstetric analgesia. Future research should focus on standardizing regimens, evaluating long-term maternal and neonatal outcomes, and overcoming implementation challenges to facilitate broader adoption.